REVIEW : Passive ring resonator micro-optical gyroscopes. (1st June 2016) - Venediktov, V Yu; Filatov, Yu V; Shalymov, E V
Abstract: This paper reviews recent advances in passive micro-optical gyroscopes. In the last decade, most research effort in the area of micro-optical gyros has been concentrated on a configuration that takes advantage of a single-mode passive ring resonator, which is usually fabricated using integrated optical technologies. The dimensions of such micro-optical gyros are comparable to those of micromechanical gyroscopes (area of 10 to 100 mm 2 ) and their sensitivity is considerably better than the sensitivity of the latter, approaching that of fibre-optic and laser gyros. Moreover, microoptical gyros can be made as a single integrated circuit, like the micromechanical gyros, but they have no movable parts, in contrast to their micromechanical counterparts. We also describe the development and investigation of micro-optical gyros produced in our studies.